Pemetaan Wilayah Kajian Kelompok Riset Pendidikan dan Dakwah: Analisis Tematik di IAIN Syekh Nurjati Cirebon - Badar, Syaeful; Hidayat, Ade (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2023)
This study aims to map the study areas and analyze research themes within research groups at IAIN Syekh Nurjati Cirebon. The findings indicate that research at IAIN Syekh Nurjati Cirebon is categorized into five main research clusters: Indonesian Studies, Islamic Studies, Social Society, Science and Technology, and Cirebonan Studies. These research fields need to be structured into leading themes that reflect the potential, characteristics, and uniqueness of research at IAIN Syekh Nurjati Cirebon. The five leading themes are: (1) Strengthening national identity and global competitiveness; (2) Enhancing awareness and understanding of Islamic perspectives to foster tolerance and peace; (3) Human development and social welfare improvement to support national integration and social harmony; (4) The advancement of science and technology with an environmental and local resource-based perspective; and (5) Strengthening culture, innovation, and creativity based on local wisdom. These leading research themes serve as guidelines for formulating research topics, development strategies, and expected outputs in the form of academic contributions or market-oriented products. Further elaboration on more specific themes is part of the research strategy aimed at advancing scientific development at IAIN Syekh Nurjati Cirebon. Moreover, the research approach is directed toward transforming Islamic studies from a monodisciplinary framework into a multidisciplinary and interdisciplinary perspective, thereby enriching scholarly discourse in the fields of education and da’wah.